Self-Control: Determinants, Life Outcomes and Intergenerational Implications - Deborah A. Cobb-Clark; Sarah C. Dahmann; Daniel A. Kamhöfer; Hannah Schildberg-Hörisch (Institute of Labor Economics (IZA), 2019)
This paper studies self-control in a nationally representative sample. Using the well-established Tangney scale to measure trait self-control, we find that people's age as well as the political and economic institutions they are exposed to have an economically meaningful impact on their level of self-control. A higher degree of self-control is, in turn, associated with better health, educational and labor market outcomes as well as greater financial and overall well-being. Parents' self-control is linked to reduced behavioral problems among their children. Importantly, we demonstrate that self-control is a key behavioral economic construct which adds significant explanatory power beyond other more commonly studied personality traits and economic preference parameters. Our results suggest that self-control is potentially a good target for intervention policies.
Keywords: D91; J24; 330; self-control; Tangney scale; personality traits; intergenerational transmission